Patient-Reported Outcomes Can Serve as a Functional Substitute for Grip Strength - Cantu, Cade A.; Myhand, Matthew; Hazime, Alaa A.; Yedulla, Nikhil R.; Day, Charles S. (Journal of Wrist Surgery, 2023)
Background Grip strength has traditionally been seen as an objective measurement of hand function, while the Patient-Reported Outcomes Measurement Information System Upper Extremity (PROMIS UE) has emerged recently as a common patient-reported outcome metric for similar purposes. The primary objective of this study was to determine if a correlation exists between grip strength, PROMIS UE, and Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH) scores in hand and upper extremity clinic patients.Methods PROMIS UE, Pain Interference (PI), and Depression (D), as well as QuickDASH were prospectively administered to patients from July 16 to September 3, 2020. A grip strength ratio (GSR), calculated by dividing the grip strength of the injured hand by that of the noninjured hand, was recorded for each individual to control for personal differences in grip strength. Data were analyzed using Spearman's correlation coefficients with the significance level at p < 0.05.Results Fifty patients participated in this study. The median GSR was 0.55. QuickDASH demonstrated strong correlations with both PROMIS UE and PI (r(48) = –0.81, p < 0.05; r(48) = 0.86, p < 0.05). GSR correlated moderately with PROMIS UE (r(48) = 0.63, p < 0.05). Finally, GSR and QuickDASH also exhibited moderate correlation with each other (r(48) = –0.62, p < 0.05).Conclusion PROMIS UE and QuickDASH are shown to correlate moderately with GSR. This suggests the PROMIS UE forms as an effective measure of hand/wrist function in hand clinic patients and may be substituted for grip strength measurements.
Keywords: outcomes; grip strength; PROMIS; QuickDASH; patient-reported outcomes